Improved biodiesel production from sludge palm oil catalyzed by a low-cost liquid lipase under low-input process conditions. (November 2021) - Loh, Jun Mann; Amelia,; Gourich, Wail; Chew, Chien Lye; Song, Cher Pin; Chan, Eng-Seng
Abstract: Sludge palm oil is a by-product produced as a result of oil loss into waste streams during the palm oil milling process. It is non-edible, inexpensive and abundantly available, thus making it an attractive feedstock for biodiesel production. However, it contains high contents of water and free fatty acids, rendering the conventional alkali-catalyzed process unsuitable. Therefore, this research aimed to improve the production of biodiesel from sludge palm oil using a low-cost liquid lipase (Eversa® Transform 2.0) produced from a genetically modified Aspergillus oryzae . The activity of the liquid lipase was determined to be 9600 IU mL −1 . We performed the reaction using low-input process conditions with only 0.2 wt% enzyme concentration and 5:1 methanol-to-oil molar ratio at a low operating temperature of 45 °C. Under an optimum stirring speed of 750 rpm, a crude biodiesel with a high ester content of approximately 94 wt% could be produced. Additionally, the crude glycerol produced has a higher purity compared to that produced via a chemical-catalyzed process. Overall, an economical and sustainable enzymatic process for the conversion of sludge palm oil into high quality biodiesel and glycerol has been demonstrated in this study. Graphical abstract: Image 1